Estimation of electron density, effective atomic number and stopping power ratio using dual-layer computed tomography for radiotherapy treatment planning. (December 2018) - Ohira, Shingo; Washio, Hayate; Yagi, Masashi; Karino, Tsukasa; Nakamura, Kenji; Ueda, Yoshihiro; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Highlights: DLCT allows to estimate electron densities and effective atomic number. DLCT system provided an accuracy to determine electron density (<0.1%). An accuracy to determine atomic number was varied widely with mean −2.0%. Stopping power ratio can be estimated with an accuracy of 0.3%. The accurate measurements could improve dose calculation in radiotherapy treatment. Abstract: Purpose: Assess the accuracy for quantitative measurements of electron density relative to water ( ρ e / ρ e, w ), effective atomic number ( Z eff ) and stopping power ratio relative to water (SPRw ) using a dual-layer computed tomography (DLCT) system. Methods and Materials: A tissue characterization phantom was scanned using DLCT with varying scanning parameters (i.e., tube voltage, rotation time, CTDIvol, and scanning mode) and different reference materials. Then, electron density ρ e / ρ e, w and atomic number Z eff images were reconstructed, and their values were determined for each reference materials. Based on these two values, SPRw was calculated. Finally, the percent error (PE) against the theoretical values was calculated for reference materials. Results: Significant linear relationships ( p  < 0.001) were observed between the measured and theoretical ρ e / ρ e, w ( r  = 1.000), Z eff ( r  = 0.989) and SPRw ( r  = 1.000) values. The PE for each reference material varied from –2.0 to 1.2% (mean, <0.1%) for electron density ρ e / ρ e, w, from –6.4 to 8.0% (mean, –2.0%) for atomic number Z eff, and from –2.0 to 1.9% (mean, 0.3%) for stopping power ratio SPRw . The mean PE of ρ e / ρ e, w (<0.1%), Z eff (<–2.5%) and SPRw (<0.4%) was verified across the variation of scanning parameters ( p  > 0.85). Conclusions: DLCT provides a reasonable accuracy in the measurements of ρ e / ρ e, w, Z eff and SPRw, and could enhance radiotherapy treatment planning and the subsequent outcomes.